Endocarditis-related stroke is not a contraindication for early cardiac surgery: an investigation among 440 patients with left-sided endocarditis. (15th October 2020) - Ruttmann, Elfriede; Abfalterer, Hannes; Wagner, Julian; Grimm, Michael; Müller, Ludwig; Bates, Katie; Ulmer, Hanno; Bonaros, Nikolaos
Abstract: OBJECTIVES: A treatment dilemma arises when surgery is indicated in patients with infective endocarditis (IE) complicated by stroke. Neurologists recommend surgery to be postponed for at least 1 month. This study aims to investigate the neurological complication rate and neurological recovery potential in patients with IE-related stroke. METHODS: A total of 440 consecutive patients with left-sided IE undergoing surgery were investigated. During follow-up, neurological recovery was assessed using the modified Rankin scale and the Barthel index. Mortality was assessed with regression models adjusting for age. RESULTS: The median follow-up time was 9.0 years. Patients with previous strokes were more likely to suffer from mitral valve endocarditis (29.5% vs 47.4%, P  < 0.001). Symptomatic stroke was found in 135 (30.7%) patients; of them, 42 patients presented with complicated stroke (additional meningitis, haemorrhagic stroke or intracranial abscess). Driven by symptomatic stroke, the age-adjusted hospital mortality risk was 1.4-fold [95% confidence interval (CI) 0.74–2.57; P  = 0.31] higher and the long-term mortality risk was 1.4-fold higher (95% CI 1.003–2.001; P  = 0.048). Hospital mortality was higher in patients with complicated stroke (21.4% vs 9.7%; P  = 0.06) only; however, mortality rates were similar comparing uncomplicated stroke versus no stroke. Among patients with complicated ischaemic strokes, the observed risk for intraoperative cerebral haemorrhage was 2.3% only and the increased hospital mortality was not driven by cerebral complications. In the long-term follow-up, full neurological recovery was observed in 84 out of 118 survivors (71.2%), and partial recovery was observed in 32 (27.1%) patients. Neurological recovery was lower in patients with complete middle cerebral artery stroke compared to other localization (52.9% vs 77.6%; P  = 0.003). CONCLUSIONS: Contrary to current clinical practice and neurological recommendations, early surgery in IE is safe and neurological recovery is excellent among patients with IE-related stroke. Clinical registration number local IRB: UN4232 382/3.1 (retrospective study). Abstract : There has been a steady increase in the incidence of infective endocarditis (IE) over the past decade due to an increase in the population at risk of IE [1, 2].